Synthesis of sign language using multimedia technique / Sharifah Norliza Syed Nariyat - Syed Nariyat, Sharifah Norliza (2004)
Synthesis of sign language's project is to produce a product of basic learning system in sign language. Base on the concern of the problem that has been face by disabled people and their family members to get the learning source of sign language, this project is one of the solutions to varies the tools of learning on this difficulties. The aimed of the project is to make an interactive system of sign language learning that can be used by all level of people. This system make learning more interesting which it replace manual instructor into one system by using multimedia technique. So many researched has been done in achieving the objectives of this project. The methodologies used on this project are project definition, creative concept, create a storyboard, application development, prototype and publish application. The implementation of this system need a lot of effort such as the software use and the knowledge on the multimedia techniques. The project will came out with an interesting interactive learning that has combination of video and 3D hand techniques. By this combination of technique, hopes it will ease the used of learning environment and as a user friendly to the learner.